KAJIAN OPINI MASYARAKAT MENGENAI KEBUTUHAN SARANA TRANSPORTASI PUBLIK DI MUARA BUNGO - Zepa Anggraini (Politeknik STIA LAN Makassar, 2019)
Discussions about public transportation are inseparable from the global definition of public transport or transportation activities that serve the public or the general public. It appears that public transportation arises because of traffic congestion effects, so that five transportation diseases arise, namely congestion, chaos, pollution (air and noise), accidents and high costs. Effective public transportation systems in some developed countries are supported by the involvement of enormous government subsidies. This study aims todetermine the level of public interest in the availability of public transportation facilities in Muara Bungo. The type of research used is descriptive quantitative research. This analysis uses data processing in the form of scoring and uses statistical analysis using SPSS software. 16. The level of public interest in the availability of public transportation facilities in Muara Bungo, based on findings from 300 sample respondents, 97% of respondents have a supporting opinionthe implementation of the Public Transportation System in Muara Bungo area. The form of preference (choice) of the Muara Bungo Moda public transportation mode, from the research findings, shows that the choice of respondents in the type of vehicle suitable for public transportation is Intermediate Bus by 43%. Theoretically, this type of research can be used as a preliminary study in developing public policy. For the Bungo District Government, it is necessary to conduct a study of the public transportation systemfeasilibily, referring to research findings that show the high interest of respondents on public transportation facilities.